Evaluation of the Effect of the Internship Training Course on the Skill of Diagnosing Common Skin Diseases among the Interns of the Dermatology Department of Hazrat Rasool Akram Hospital Using Computer-assisted Assessment (CAA) Method (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Internship is a crucial period of the general medicine doctorate that plays a key role in shaping the basic skills and professional abilities of medical students and is a major part of the educational programs in this field. It is also essential in better preparing medical students for their future professional roles. Clinical evaluation and the use of methods capable of measuring the skills, competencies, and abilities of students are of special importance. Therefore, the aim of this study was to investigate the effect of the internship training course on the diagnosis of common skin diseases using the computer-assisted assessment method (CAA).Method: In this pre-experimental study, one-group pre- and post-testing were performed, and the efficacy of the internship training course on the skill of diagnosing common skin diseases was investigated among the interns of the dermatology department of Hazrat Rasool Akram Hospital, Tehran, Iran, from October 2018 to March 2020. To conduct this study, a Computer-Assisted-Assessment (CAA) test in the form of a PowerPoint presentation consisting of typical images of 25 common skin diseases at the time of entry and also a similar test of typical but different and cluttered images of the same 25 common skin diseases was performed on the last day of each internship course, and the interns recorded the diagnosis of the diseases displayed on the answer sheet during a fixed period of time. Then, the pre-and post-testing information was recorded during the consecutive periods of the interns' presence in the dermatology department. This information included the exam scores, age, sex, marital status, months of internship, year of entering the university, being an international campus student, and month of completing the internship period. After analyzing the data, the effectiveness of the training received during the internship period was assessed.Results: In this study, 252 medical students with an average age of 25.35 ± 2.0 years were investigated. Among the participants, 32 people (12.7%) were international campus students, and 220 people (87.3%) were non-campus students. Also, 56 students were married (22.2%), and 196 participants (77.8%) were single. The average score of interns before the course was 8.19±2.6, and after the course was 19.39±3.4, and the difference between them was significant (P<0.001). Also, the mean difference between the scores before and after the training course was 11.19 +/- 2.1 and the scores of all participants in the study increased after the training course, which ranged from 3 to 17 scores. Pre- and post-course scores in single people were significantly higher compared to married people (P<0.001 for both). However, there was no significant difference between mean grade changes of pre-and post-course scores in single and married people (P=0.092). Also, pre-and post-course grades and grade changes in the international campus students were significantly lower than other interns (P<0.001). On the other hand, there was a significant relationship between being an international campus student and grades before the course (P=.005), grades after the course (P<0.001), and grade changes (P<0.001).Conclusion: Our results showed that the internship training course of the dermatology department of Hazrat Rasool Akram Hospital would efficiently increase the ability to diagnose common skin diseases by interns. This study also showed that the pre-course and post-course scores and their changes in international campus students are significantly lower compared to other students. Also, older age and being married reduce the pre-course and post-course scores in interns compared to others.